2014
DOI: 10.3938/jkps.65.92
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric properties and microwave sintering of BaTiO3 synthesized by using the alkoxide-hydroxide sol-gel process

Abstract: BaTiO3 nanopowder was synthesized at low temperature by using an alkoxide-hydroxide sol-gel method and were sintered by microwave processing. Microwave sintering of BaTiO3 was carried out at different temperatures for 20 min to get dense ceramics. The phases, morphologies, crystal structures and weight losses of the synthesized and sintered materials were characterized by using Xray diffraction (XRD), Field-emission scanning electron microscope (FE-SEM), Raman spectroscopy and Thermo-gravimetric analyzer (TGA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…In this study, BaTiO 3 -Ni nanopowder shows higher breakdown strength than BaTiO 3 -Ni paste and it decreased with increasing metal concentration. Shin and Kim reported the electrical breakdown strength of monolithic BaTiO 3 (7.5 kV/mm) [31,32]. Halder et al showed that the breakdown strength decreased with increasing silver content compared to pure BaTiO 3 , which is consistent with the fact that the conductive particles shorten the internal electrode distance leading to an increase in the effective electric field, but simultaneously decrease the breakdown strength [33].…”
Section: Resultssupporting
confidence: 51%
“…In this study, BaTiO 3 -Ni nanopowder shows higher breakdown strength than BaTiO 3 -Ni paste and it decreased with increasing metal concentration. Shin and Kim reported the electrical breakdown strength of monolithic BaTiO 3 (7.5 kV/mm) [31,32]. Halder et al showed that the breakdown strength decreased with increasing silver content compared to pure BaTiO 3 , which is consistent with the fact that the conductive particles shorten the internal electrode distance leading to an increase in the effective electric field, but simultaneously decrease the breakdown strength [33].…”
Section: Resultssupporting
confidence: 51%
“…Lead-based ceramic materials such as lead-zirconate-titanate (PZT) have dominated the piezoelectric market because of their ease of fabrication, low cost, and outstanding ferroelectric and dielectric properties with high curie temperatures of 390 °C [ 1 ]. The PbTiO 3 -PbZrO 3 system is the most notable piezoelectric material for actuators, transducers, and sensors [ 1 , 2 , 3 ]. The high concentration of lead (>50%) and the toxicity of highly volatile PbO during sintering made these materials unsafe for the environment and human health.…”
Section: Introductionmentioning
confidence: 99%
“…These fillers may also improve the dielectric properties of polymers . Dielectric properties of polymers have not been studied much in literature, currently it is more famous about ceramics‐based materials . In this study, polypropylene (PP) has been reinforced with oyster shell powder to study its effects on thermal stability, fire retardancy, dielectric properties, optical parameters, and mechanical properties of polypropylene.…”
Section: Introductionmentioning
confidence: 99%